EDUKASI CEGAH PENYAKIT TIDAK MENULAR DENGAN CERDIK DAN PATUH DI ERA PANDEMI - Dani Prastiwi; Metha Anung Anindhita; Heri Pornomo (LPPM Universitas Pekalongan, 2021)
Non-Communicable Disease (NCD) have a very high risk of being infected with Covid-19. NCD’s control has actually been carried out through the activities of the Posbindu, but due to the Covid-19 pandemic with restrictive rules, the Posbindu could not be implemented. This service aims to educate health cadres and increase public awareness in controlling NCD’s. The activity was attended by 10 participants who are health cadres. The focus of this service activity is on promotive and preventive through education about CERDIK and PATUH behavior to prevent NCD’s in the Covid-19 pandemic era. The result of this service is that health cadres have understood the material presented. Health cadres want further activities to be carried out regarding the simulation of Posbindu activities in the Covid-19 pandemic era. Through this activity, it is hoped that it can awaken the role of health cadres to be able to socialize the public about CERDIK and PATUH behavior so that prevention and control of NCD’s can still be carried out. Keyword : Education, Non Communicable Disease